Single Seminal Vesicle Metastasis From Dorsal Melanoma Detected by 18F-FDG PET/CT and Confirmed by Biopsy. (11th March 2023) - Testart Dardel, Nathalie; Isenborghs, Elsa; Valerio, Massimo; Michielin, Olivier; Schaefer, Niklaus
Abstract: This case shows an unusual presentation of a melanoma metastasis, visualized by 18 F-FDG digital PET/CT, with a single abnormal focal uptake in the right seminal vesicle. Histologic analysis confirmed a melanoma metastasis, subsequently treated by stereotactic radiation therapy. We illustrate an unusual and single-site millimetric melanoma metastasis detected by 18 F-FDG PET/CT, highlighting the high performance of state-of-the-art digital PET/CT and the importance of a multidisciplinary approach in treatment and follow-up of melanoma patients. In this case, histological diagnosis was essential for correct diagnosis and adequate clinical management of the patient.